Introducing a Method of In Vitro Testing of Different Anchoring Systems Used for Female Incontinence and Prolapse Surgery. (22nd December 2013) - Anding, Ralf; Tabaza, Ruth; Staat, Manfred; Trenz, Eva; Lohmann, Philipp; Klinge, Uwe; Kirschner-Hermanns, Ruth
Abstract : Aims . To develop a method for in vitro testing to compare different intracorporeal anchoring systems (AS) used, for example, in single-incision slings or vaginal meshes. Intracorporeal fixation needs reliable anchorage systems, which keep the implant in the operative and early postoperative phase in place. Up to now, the impact of the design of current anchor systems and their capability to provide sufficient retention forces is not known. Methods . Four AS ("PelFix", "Surelift", "TFS", and "MiniArc") were evaluated in an animal model and a ballistic gelatine model with pull-out tests. We performed ANOVA with post hoc Bonferroni. Results were presented as mean values whereby a significance level of <0.05 was considered significant. Results . The four systems showed significantly different pull-out forces. Depending on mesh structure, size, and form of the AS, mechanical strain resulted in deformation with local peak stresses. Under the condition of form stability, relative differences of pull-out forces did not change in different tissues. Conclusions . Reliable testing of different AS in their ability to keep mesh implants in place can be done in animal models and in especially designed ballistic gelatine. These methods of testing will help to modify AS in novel pelvic floor implants.